Perancangan Aplikasi Tutorial Cake Berbasis Android Untuk Meningkatkan Pendapatan Usaha Ibu Rumah Tangga di Wilayah Batu Bara - Sarli Marlina Damanik (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
Some people choose to use gadgets instead of books or other printed media. Public awareness of the dangers of ingredients containing synthetic chemical substances in cakes has gradually begun to open and be awakened. People are now starting to like to make their own cakes because it saves money and is healthier. Making your own cake can also hone people's creativity because innovation is not only for the world of technology but with this creativity it can generate income for housewives. However, the current problem is that housewives living in the Batu Bara area do not understand how to make cakes to increase income in their household, even though by using Android-based smartphones they can be creative in making cakes. The purpose of this research is to create an Android-based cake tutorial application to increase the business income of housewives in the Batu Bara area. The data used in this study are in the form of cake type data, material data, and data on the cake-making process, the results obtained from this study are in the form of an application that can provide information on the ingredients used in making cakes and the steps taken to make cake.